Incompatibility of Bad Debt "Expense" With Contemporary Accounting Theory. - Cramer, Joe J. (The Accounting Review, 1972)
The article discusses the incompatibility of bad debt "expense" with contemporary accounting theory. Accounting treatment of bad debt expense is inconsistent with criteria deemed relevant for measuring operating income in accordance with contemporary accounting theory. Bad debt expense is reflected in the income statement along with other information concerning operations even in spite of the fact that it originates as non-service data. This is to say that bad debt expense is not homogeneous with other costs experienced by the entity which comprise the basic data for periodic matching with. The following analysis delineates the methodological inconsistency, and a more appropriate accounting procedure for bad debt expense is proposed. Accounting methodology prescribes the relevant set of data for approximating periodic income from operations. Elemental data constituting the set are presumed to consist of services received and services rendered by an entity for which an evaluation of operations is made.